Adiponectin plasma levels in patients with age-related dementia - Kaiyrlykyzy, A.; Umbayev, B.; Masoud, A.; Shramko, A.; Idrissova, D.; Zhussupova, A.; Alzhanova, D.; Alimbetov, D.; Askarova, S. (My University, 2016)
Adiponectin play a significant role in the regulation of type 2 diabetes, obesity, atherosclerosis, non-alcoholic fatty liver disease and neurodegenerative disorders. Evidence suggests that adiponectin may be an independent risk factor for all-cause dementia and Alzheimer's disease (AD) and the level of adiponectin in plasma reflects its level in cerebrospinal fluid (CSF). Studies demonstrated that elevated adiponectin level in blood was associated with an increased risk of dementia and AD in women and indicates that the sex dimorphism with regard to adiponectin levels association with Alzheimer's disease was clearly observed
Keywords: Adiponectin; dementia; Alzheimer's disease